KAMPANYE PENCEGAHAN HIV/AIDS MENGGUNAKAN BUKU SAKU PADA REMAJA DI PONDOK PESANTREN MAMBA’U SYAFA’ATIL QUR’AN KOTA BLITAR - Parensa, Viola Izzah; Winarni, Sri; Djuwadi, Ganif; Rachman, Mohammad Zainol (Poltekkes Kemenkes Malang, 2024)
HIV stands for Human Immunodefciency Virus, a virus that causes reduced immunity in humans, or the virus that causes AIDS. Based on preliminary studies conducted at the Sananwetan Health Center, there are indicators of Islamic boarding school PHBS that have not been achieved, namely education about HIV/AIDS among adolescents at the Mamba'u Syafa'atil Qur'an (MSQ) Islamic Boarding School. The purpose of this study was to identify HIV/AIDS prevention campaigns using pocket books for adolescents at the Mamba'u Syafa'atil Qur'an Islamic Boarding School in Blitar City. This research method uses quantitative methods with pre-experimental designs with a one-group pretest-posttest design. The population in this study were adolescents of MSQ Islamic Boarding School in Blitar City totaling 35 people with total sampling technique. The research was conducted on February 24 - March 11, 2023, the research instrument was a knowledge and attitude questionnaire with a Likert Scale. The results of the Paired Sample t-test showed a significance level of p-value = 0.00, which means that this study rejects H0. Thus, the HIV/AIDS prevention campaign using a pocket book affects the knowledge and attitudes of adolescents. It can be seen that there is an increase of 19% in the level of knowledge and an increase of 14% in the attitude of adolescents of Pondok Pesantren Mamba'u Syafa'atil Qur'an towards HIV/AIDS prevention.